Population genetics of a climate-indicating predator across the forest-tundra ecotone - Derek Taylor (Arctic Data Center, 2017)
Subarctic freshwater lakes and ponds in Alaska are important oases for polar biodiversity and resources for arctic peoples. However, this habitat is also among the most sensitive to disturbances such as heavy metal pollution, eutrophication, and drainage or desiccation from climate warming. Environmental indicator species in freshwater have both acted as sentinels for ongoing change and as proxies for historical change. Phantom midges (Chaoborus), for example, are among the most important freshwater dipterans for aquatic toxicology and for indicating a boreal zone climate. In some cases, Chaoborus is believed to be a better sentinel of boreal forest-tundra boundary changes than the tree line because trees can have a growth lag that is negligible in midges. The larvae of Chaoborus are also voracious predators of microcrustaceans and, as such, can strongly affect the species compositions of freshwater habitats. The PI has recently found that two species of Chaoborus are common well beyond the tree line in roadside ponds of the Seward Peninsula of northwestern Alaska. This finding provides an opportunity to improve understanding of how tundra lakes and ponds may change as they encounter a keystone predator of the boreal zone. Moreover, the effect of direct human disturbances such as road construction on the freshwaters of the boreal zone ? tundra boundary can be assessed. Several aspects of the biology of Chaoborus in subarctic North America are poorly known. Because there are slight morphological differences between tundra species and well-studied temperate species, the geographic source and even the species name of the tundra populations are unclear. One objective of this research is to test hypotheses about the genetic affinities of Chaoborus that are presently found on the tundra. This involves phylogenetic comparisons of tundra specimens with those from eastern Asia, and with boreal Alaska. Another goal is to test the hypothesis that road construction has facilitated the expansion of boreal zone Chaoborus deep into the tundra. Testing this hypothesis involves testing for the erosion of genetic diversity on tundra ponds compared to forest ponds with high-resolution genetic markers. This project will also carry out paleoecological assessments of the rate and mode of colonization of tundra ponds. This research will inform environmental biologists, fisheries managers, engineers and planners about the role of human disturbance on the freshwater ecosystems across the tundra-boreal forest boundary at a critical time. The project will enhance or even enable comparative studies of environment-indicating chaoborids and promote a deeper understanding of recent and ongoing anthropogenic change in subarctic freshwaters. The speed and mode of colonization of tundra ponds by Chaoborus midges is important to paleoecology but unknown.